DSC650: Data Technology and Future Emergence / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2018)
The course will give the students to explore key data analysis and management techniques, which applied to massive data sets are the cornerstone that enables real-time decision making in distributed environments, business intelligence in the Web, and scientific discovery at large scale. In particular, the students will examine the map-reduce parallel computing paradigm and associated technologies such as Hadoop distributed file systems, and no sql databases.